Tari Rentak Kudo Dari Ritual Panen Ke Hiburan Di Desa Tanjung Sungai Penuh - Yedes Ratmi; Nerosti Nerosti (SENDRATASIK UNP, 2021)
This study aims to analyze the change in the function of Rentak Kudo Dance from harvest rituals to entertainment in Hamparan Rawang Subdistrict, Sungai Penuh City. The analysis focused on Rentak Kudo dance performances in entertainment events at weddings. This type of research is qualitative with descriptive analytical methods. The object of the research is Rentak Kudo Dance in Hamparan Rawang Subdistrict. The main instrument is the researcher himself who assisted with the tool in collecting data in the field in the form of stationery and photo cameras. Data collection techniques in the form of literature studies, observations, interviews and documentation. Data analysis techniques are by collecting data, analyzing data, sorting the appropriate data changes in the function of Rentak Kudo Dance and then describing the appropriate issues discussed. The results of the study that Rentak Kudo Dance used to be displayed at the harvest ritual event in Hamparan Rawang Kota Sungai Penuh, with certain requirements both choose dancers 6 women and 6 men, the floor pattern is only a straight line, and the music pegiring Dance Rentak Kudo used only tambourines only. Dancers are also obliged to perform rituals of flowers, oranges and frankincense. The offering is paired with the body of a dancer. As for the change in the function of Rentak Kudo Dance as entertainment at the wedding in the evening, the performance of Rentak Kudo Dance undergoes a change in mass form with the accompaniment of remix/ DJ music with a single organ. This dance has undergone very different changes that are social and entertainment, which are popular among the local community.